Synthesis of Titanium Containing SBA-15 and Its Application for Photocatalytic Degradation of Phenol - Lili Yang; Zeyu Jiang; Sufeng Lai; Chongwen Jiang; Hong Zhong (International Journal of Chemical Engineering)
We synthesized Ti-containing SBA-15 by one-pot hydrothermal method and extensively investigated its physicochemical properties and examined its photocatalytic activity to degrade phenol. It’s shown that appropriate amount of titanium could be effectively incorporated into the framework of SBA-15 without provoking structure change and the tetrahedrally coordinated titanium species were well-ordered in Ti-incorporated SBA-15. Under UV-irradiation, the Ti-containing SBA-15 exhibits good photocatalytic activity for phenol degradation in the simulated waste water. The higher photocatalytic activity of Ti-containing SBA-15 to degrade phenol was ascribed to the more titanium content and anatase titanium dioxide. In addition, the new photocatalyst displays a good regeneration and cyclic performance after six runs.